2021
DOI: 10.2147/ndt.s275750
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Challenges in Outpatient Stroke: Stroke Chameleons and Atypical Stroke Syndromes

Abstract: Failure to diagnose transient ischemic attack (TIA) or stroke in a timely fashion is associated with significant patient morbidity and mortality. In the outpatient or clinic setting, we suspect that patients with minor, transient, and atypical manifestations of cerebrovascular disease are most prone to missed or delayed diagnosis. We therefore detail common stroke chameleon symptoms as well as atypical stroke presentations, broadly review new developments in the study of diagnostic error in the outpatient sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 107 publications
(172 reference statements)
1
12
0
Order By: Relevance
“…The symptoms reach their peak within minutes or hours of onset. As earlier alluded to, the nature of symptoms as well as their severity depends on the artery involved [ 19 ]. Failure to provide quick interventions can endanger the patient's life [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms reach their peak within minutes or hours of onset. As earlier alluded to, the nature of symptoms as well as their severity depends on the artery involved [ 19 ]. Failure to provide quick interventions can endanger the patient's life [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, symptoms such as vertigo, dysphagia, gait disturbance, nystagmus, cranial nerve palsies, and ataxia are not adequately assessed by the NIHSS score [13]. On the other hand, such symptoms associated with posterior circulation stroke may lead to an under-recognition of this pathology by clinicians, as well as other less common symptoms, such as nausea and vomiting, imbalance, ill-defined dizziness, and isolated vertigo [14,15]. Physicians must consider that patients presenting at the emergency department with a low NIHSS score may have a posterior circulation stroke.…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in a study comparing 156 consecutive stroke patients misdiagnosed in an emergency department in Sydney, Australia, which found that patients who experienced stroke misdiagnosis were commonly FAST-negative and displayed non-specific or atypical symptoms ( 70 ). The problem of stroke misdiagnosis has seen calls for a broadening of the symptoms being considered during the initial stroke diagnosis period and improvements to the diagnosis process itself ( 69 , 71 ). Studies into the adoption of utilizing BE-FAST (Balance, Eyes, Face, Arms, Speech, and Time) as a wider screening technique in acute intervention found that this helped reduce the amount of missed strokes ( 72 , 73 ).…”
Section: Discussionmentioning
confidence: 99%